Hydrogen embrittlement in nickel-based superalloy 718: Relationship between γ′ + γ″ precipitation and the fracture mode. (21st December 2015) - Rezende, M.C.; Araujo, L.S.; Gabriel, S.B.; dos Santos, D.S.; de Almeida, L.H.
Abstract: The present work studies the influence of different metallurgical conditions on the hydrogen embrittlement of the nickel-based superalloy 718. The interaction of hydrogen with the microstructure and the effects on its properties were evaluated by means of tensile tests and fracture analysis. The samples were submitted to cathodic hydrogenation for 21 days. The results were compared with non-hydrogenated tensile samples. Permeation and diffusion, as well as proper activation energies were determined by gaseous permeation tests from 300 to 422 °C. The results show that the degree of embrittlement was more pronounced for in aged condition in the presence of γ′ and γ″ precipitation, as compared with the solution annealed condition, despite the limited depth of hydrogen penetration in the cathodically charged samples. Regarding the permeation tests, the diffusion and permeation of hydrogen was influenced by the microstructure, particularly the precipitation of γ′, γ″ and δ phases. The aged and overaged conditions presented lower values of diffusivity and permeability, in comparison to the solution annealed condition. Highlights: Mechanical properties were affected by H in solution annealed and aged conditions. Permeability and diffusivity were affected by the precipitation of phases (γ′, γ″, δ). For same condition with H and without H, no change in fracture mode was observed.